Lone star nation how a ragged army of volunteers won the battle for Texas independence - and changed America - Brands, H. W.; Random House Audio (New York : Random House Audio ; Prince Frederick, Md. : Distributed by Recorded Books, 2004)
Brands writes the story of Texas's precarious journey to statehood, from its early colonization in the 1820s to the shocking massacres of Texas loyalists at the Alamo and Goliad by the Mexican army, from its rough-and-tumble years as a land overrun by Comanche to its day of liberation an upstart Republic
Read by : Chuck Montgomery
Keywords: Texas -- History -- Revolution, 1835-1836; Texas -- History -- To 1846; Texas -- History -- 1846-1850